2022
DOI: 10.2174/2210315511666210906114009
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils: A Novel Approach for Anti-Microbial Therapy

Abstract: : Overexploitation of antibiotics has led to significant challenges with antimicrobial resistance. The gravity of this trend has resulted in the rapid emergence of multi-resistant pathogens. Increased frequency to treat infections and the unfeasibility to reverse this resistance have burdened researchers in developing novel mechanisms to counteract and obstruct antimicrobial resistance. An effective medical strategy to control resistance was to develop new and potent antibiotics although, a sobering reality is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Antimicrobial agents come from a variety of sources, such as microbes, insects, plants, fishes, mollusks, etc. [20][21][22][23][24]. Recently, the discovery of cyclic peptide antibiotics derived from microorganisms has become a new research hotspot, attracting the attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial agents come from a variety of sources, such as microbes, insects, plants, fishes, mollusks, etc. [20][21][22][23][24]. Recently, the discovery of cyclic peptide antibiotics derived from microorganisms has become a new research hotspot, attracting the attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the search for an alternative strategy with greater efficacy is an urgent medical need. Several studies have investigated the use of antibiotics in combination with major essential oil (EO) compounds [ 16 , 17 , 18 , 19 , 20 , 21 ]. They have revealed that this approach could be efficiently used in therapy to overcome any resistance to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…They have revealed that this approach could be efficiently used in therapy to overcome any resistance to antibiotics. Nowadays, some researchers reported that essential oils have the capacity to act as resistance modifying agents and thereby enhance the efficacy of antibiotics [ 20 ]. Based on these facts and on our previous studies [ 16 , 21 ] of the combination of AMX with 1,8-cineole EO, a major compound used to combat ESBL bacterial resistance, we have conducted an in vivo experiment to study the pharmacokinetics and pharmacodynamics of AMX combined with 1,8-cineole using a rabbit model.…”
Section: Introductionmentioning
confidence: 99%